Leitura, cognição e inferência das consignas didáticas das atividades de compreensão textual - Matos, Kleydiane da Graça Feitosa (2021)
Recognized for its importance in the development of numerous student skills, reading is a process consisting of stages, which goes from the phonological to the pragmatic level of language. Due to its complex nature, it brings together multiple processes that demand the activation of different strategies that promote the acquisition and automation of more elaborated competences, such as the inference of the meaning of the words arranged in a text. In the classroom universe, one of the difficulties of the students is the comprehension of the didactic slogans that constitute the orientations provided in the didactic book, fundamental for the students to succeed in carrying out the actions recommended in these statements. Given the relevance of understanding didactic slogans in the lives of students, this dissertation focuses, as recommended by Marcuschi (2002) on textual genres, the textual genre didactic slogan present in the textbook adopted by the Municipal Elementary School Olga Benário, from a study of its structure and functioning, in order to value the role that students need to assume in different teaching-learning situations. From the theoretical-methodological point of view, it is proposed, in the light of the studies by Dolz, Noverraz and Schneuwly (2004), a didactic sequence, whose motivating text is the short story, as a methodology used in the product Didactic Notebook aimed at working with students of the 6th year A of elementary education of the said Teaching Unit. As a source of bibliographic research, publications are considered, among others, authors such as Barbosa and Carlberg (2014), Ferreira (2007), Fonseca (2014) and Riestra (2004), whose works focus on the study of didactic slogans and, more globally, for mother tongue or foreign language teaching.